Economic and social turbulence in Greece: The product markets are a no-brainer, the labour market is not - Michael Mitsopoulos; Theodore Pelagidis (Intereconomics, 2009)
Since the 1990s the Greek economy has posed a unique international paradox, combining relatively strong growth rates with a very weak performance on many other fronts ranging from poor labour and product market institutions and low competitiveness to poor environmental protection and high levels of corruption. The recent economic and social turbulence in Greece is a result of this paradox. What is the explanation for this situation? What reforms are necessary to change it?
Keywords: 330